Career Intention of Hospitality students: Critical Role of Industrial Training - R. Shreelatha,; Heggde, Githa (International Journal of Psychosocial Rehabilitation, 2020)
The tourism and hospitality industry is one of the largest components under the services sector of our Indian economy. Hotels are indeed an integral part of tourism industry. The Indian hospitality sector is growing at a cumulative annual growth rate of 14% every year, thereby adding considerable amount of foreign exchange to the economy. There is enormous opportunities of growth in the tourism and hospitality sector with the gross annual demand for manpower crossed 5 lakh in 2010 and is expected to reach 920000 in 2020. This study tries to identify the factors that impact the career intention of the students from their industrial training. From the data collected from the AICTE approved colleges in Karnataka, it was observed that Academic inputs & academic supervision, experiences from industrial training had a significant impact on the career intention of the hotel management students